1993
DOI: 10.1139/t93-073
|View full text |Cite
|
Sign up to set email alerts
|

pH influence on selectivity and retention of heavy metals in some clay soils

Abstract: The problem of varying species of heavy metals existing as individual species or in combination with each other in simulated contaminant leachates (solutions) is studied in relation to selectivity and retention in four different kinds of soil. The influence of pH on the retention characteristics is also examined. The results obtained from the heavy metals single-species and composite-species adsorption tests indicate that in evaluating the attenuation potential of the soil substrate (i.e., contaminant attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 0 publications
2
49
0
6
Order By: Relevance
“…Extracts were combined and stored at 4 � C prior to analysis of ex changeable Pb (E1Pb), with concentration being corrected for occluded/pore water E1Pb. The amount of sorbed Pb that was not exchanged by the NaNO 3 washes was operationally defined as being specifically sorbed or sorbed to high affinity sites (Yong and Phadungchewit, 1993). The I of the soil solutions was readjusted to 0.01 M via two 30 mL washes with 0.01 M NaNO 3 , shaking for 1 h during each rinse.…”
Section: Sequential Addition Of Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracts were combined and stored at 4 � C prior to analysis of ex changeable Pb (E1Pb), with concentration being corrected for occluded/pore water E1Pb. The amount of sorbed Pb that was not exchanged by the NaNO 3 washes was operationally defined as being specifically sorbed or sorbed to high affinity sites (Yong and Phadungchewit, 1993). The I of the soil solutions was readjusted to 0.01 M via two 30 mL washes with 0.01 M NaNO 3 , shaking for 1 h during each rinse.…”
Section: Sequential Addition Of Metalsmentioning
confidence: 99%
“…Thus, coulombic-type interactions are favored with other charged species or surfaces for Ca 2þ and Cd 2þ . Echeverria et al (1998) and Yong and Phadungchewit (1993) reported on the competitive sorption of various heavy metals in mineral and soil systems. They reported decreased sorption of Cd, Cu, Pb, and Zn when these metals were added together compared to when they were added alone to soils.…”
Section: Pb CD and Ca Interactionsmentioning
confidence: 99%
“…The authors (Yong et al 1990) proved that high Pb uptake by the clays could affect the buffer capacity and the Pb retention capacity. In the paper (Yong and Phadungchewit 1993), it has been demonstrated that high amounts of heavy metals are retained in the soils if the soil buffer capacity remains high enough to resist a change in pH. The results from the selective sequential extraction analysis of heavy metals supported also the conclusion of the significance of soil buffer capacity with regard to heavy-metal retention (Yong and Phadungchewit 1993).…”
Section: Natural Attenuation/intrinsic Chemical Remediation Of Metalsmentioning
confidence: 89%
“…In the paper (Yong and Phadungchewit 1993), it has been demonstrated that high amounts of heavy metals are retained in the soils if the soil buffer capacity remains high enough to resist a change in pH. The results from the selective sequential extraction analysis of heavy metals supported also the conclusion of the significance of soil buffer capacity with regard to heavy-metal retention (Yong and Phadungchewit 1993). The capacity of the soils to retain high amounts of heavy metals as they receive increasing amounts of acid (i.e., as the pH is reduced) depended directly on the soil initial pH values and on their buffer capacities.…”
Section: Natural Attenuation/intrinsic Chemical Remediation Of Metalsmentioning
confidence: 99%
“…A cation with high selectivity for a particular soil surface (exchanger) will be preferentially adsorbed relative to one with lower selectivity. Many studies, considering sorption of heavy metals (i.e., Pb, Cu, Zn, Cd, and Ni) added to soils and pure minerals (i.e., goethite, alumina, kaolinite, and zeolite), have inferred higher Pb selectivity relative to other heavy metals based on differences in total amount of metals sorbed or desorbed (Ahmed et al, 1998;Gao et al, 1997;Pardo, 2000;Yong and Phadungchewit, 1993). These studies did not focus on the exchangeable Pb fraction.…”
mentioning
confidence: 99%